Prevalence of mismatch repair-deficient crypt foci in Lynch syndrome: a pathological study - Kloor, Matthias; Huth, Cathrin; Voigt, Anita Yvonne; Benner, Axel; Schirmacher, Peter; Knebel Doeberitz, Magnus von; Bläker, Hendrik (The lancet. Oncology, 2012)
Summary Background Lynch syndrome is an inherited tumour predisposition syndrome caused by germline mutations of DNA mismatch repair (MMR) genes. Mutation carriers have a high risk of developing colorectal cancer, but do not present with polyposis, a typical feature of other colorectal cancer syndromes such as familial adenomatous polyposis, in which polyposis reflects the high frequency of biallelic APC gene inactivation. We asked whether in Lynch syndrome biallelic inactivation of MMR genes occurred at a similar frequency to that of APC gene, and whether MMR inactivation resulted in detectable lesions within the intestinal mucosa. Methods Resections done for small and large bowel cancer between January, 2002, and January, 2011, were retrieved. We systematically analysed non-tumorous mucosa from carriers of a Lynch syndrome mutation (set 1: ten patients) and control patients without Lynch syndrome (set 1: nine patients) for MMR protein expression (MLH1, MSH2, and EPCAM) with immunohistochemistry. We validated the findings in an independent sample set (set 2: 30 Lynch syndrome patients, 79 controls). We did an analysis of microsatellite instability by PCR analysis to test lesions for mismatch repair deficiency. We applied a Poisson regression model to analyse the distribution of MMR-deficient crypt foci counts and a Fisher's exact test to compare the prevalence of these foci between mutation carriers and control patients. Findings 20 crypt foci with no MMR protein expression were detected in 20·1 cm2 of non-tumorous mucosa from Lynch syndrome patients (set 1), an additional five were detected upon resectioning of two samples. In an independent validation set (set 2), two MMR-deficient crypt foci were noted in 2·2 cm2 of mucosa. No MMR-deficient crypt foci were noted in non-tumorous mucosa from control patients without evidence for Lynch syndrome (set 1: 3·7 cm2, set 2: 4·8 cm2). Microsatellite instability was detected in all seven MMR-deficient crypt foci analysed. A subset of these foci displayed unusual architectural and cytological abnormalities, although they had no polypous or adenomatous appearance. Interpretation We identified a novel type of lesion, the MMR-deficient crypt focus, as the manifestation of biallelic MMR gene inactivation in Lynch syndrome. The abundance of MMR-deficient crypt foci indicates a high frequency of biallelic MMR gene inactivation, which is in sharp contrast with the low number of clinically manifest cancers in Lynch syndrome. This discrepancy suggests that most MMR-deficient crypt foci do not progress to cancer. We propose Lynch syndrome as a unique model syndrome for studying initial steps of MMR deficiency, tumour initiation and, possibly, elimination. Funding German Cancer Aid and German Research Foundation.
Gesehen am 12.10.2018